2022
DOI: 10.1186/s12935-022-02445-w
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic value of the Fibrinogen to pre-albumin ratio in malignant tumors of the digestive system: a systematic review and meta-analysis

Abstract: Background In recent years, the Fibrinogen to pre-albumin ratio (FPR) has been reported in many studies to be significantly associated with the prognosis of various cancers. This systematic review and meta-analysis aimed to investigate the prognostic value of FPR in malignant tumors of the digestive system based on available evidence. Methods The relevant articles published before July 1, 2021, were systematically retrieved from electronic database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Our study showed that lGIP was more likely to occur in the patients with GIP having FIB levels ≥ 4.920 g/L than those having FIB levels < 4.920 g/L. Recently, studies have reported that there are high FIB levels in pancreatic cancer, colorectal cancer, and other gastrointestinal system malignancies [ 23 , 24 ], suggesting that the baseline FIB level may be high in patients with tumor-induced lGIP.…”
Section: Discussionmentioning
confidence: 57%
“…Our study showed that lGIP was more likely to occur in the patients with GIP having FIB levels ≥ 4.920 g/L than those having FIB levels < 4.920 g/L. Recently, studies have reported that there are high FIB levels in pancreatic cancer, colorectal cancer, and other gastrointestinal system malignancies [ 23 , 24 ], suggesting that the baseline FIB level may be high in patients with tumor-induced lGIP.…”
Section: Discussionmentioning
confidence: 57%
“…Previous Mate analysis pointed out that FPR has a high prognostic value for malignant tumors of the digestive system. 25 Xie et al found that FPR is an independent prognostic factor for resectable colorectal cancer. 26 In addition, similar conclusions have been drawn in digestive system tumors such as gastric cancer, pancreatic cancer, esophageal cancer, and so on: the prognosis of patients tends to become worse with the increase of FPR.…”
Section: Discussionmentioning
confidence: 99%
“…Fib is a proin ammatory protein and an important substance in coagulation and thrombosis. The level of Fib re ects the hypercoagulable state of blood, which indicates hematogenous and lymph node metastasis or deeper tumor invasion [31][32][33]. The combination of ROS, reactive nitrogen species (RNS), IL-6, and JAK induces DNA damage leading to genetic instability through the STAT-3 pathway, promoting cancer cell proliferation and angiogenesis [34][35][36].…”
Section: Discussionmentioning
confidence: 99%